2022
DOI: 10.1038/s41598-022-14161-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome analysis of 177 pediatric patients with undiagnosed diseases

Abstract: Recently, whole-exome sequencing (WES) has been used for genetic diagnoses of patients who remain otherwise undiagnosed. WES was performed in 177 Japanese patients with undiagnosed conditions who were referred to the Tokai regional branch of the Initiative on Rare and Undiagnosed Diseases (IRUD) (TOKAI-IRUD). This study included only patients who had not previously received genome-wide testing. Review meetings with specialists in various medical fields were held to evaluate the genetic diagnosis in each case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…WES can be applied in children with refractory epilepsy or epileptic encephalopathy ( 29 , 30 ). One study cohort consisted of 177 undiagnosed Japanese patients and yielded a 44% genetic diagnosis rate in children with complex diseases ( 31 ). However, for complex disorders, such as HS with other comorbidities, was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…WES can be applied in children with refractory epilepsy or epileptic encephalopathy ( 29 , 30 ). One study cohort consisted of 177 undiagnosed Japanese patients and yielded a 44% genetic diagnosis rate in children with complex diseases ( 31 ). However, for complex disorders, such as HS with other comorbidities, was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recommendations, the genetic background of AS can be investigated using methods that are endorsed by geneticists and reimbursed, such as FISH, aCGH microarray, or molecular analysis of the UBE3A gene sequence. WES testing should be reserved for rare cases with diagnostic di culties that cannot be detected by other molecular methods 17,18 . The WES test cannot unambiguously assess the most common cause of AS, which is abnormalities in the methylation pattern of the critical 15q11-q13 region associated with AS.…”
Section: The Wes Studymentioning
confidence: 99%
“…Feliciano et al [15] reported that the diagnostic yield of ES for detecting SNVs/indels and CNVs in ASD was 10.4% in 457 families. Although the diagnostic rate of ES depends on the cohort and target disease that is being assessed, its rate in ASD is lower than that in other genetic conditions, which have usually been reported as 25%-44% [16,17]. However, many aberrant disease-causing genes have been identified over the years, and 10-15% of unresolved cases may obtain a molecular diagnosis by reanalysis (reviewed by Lee and Nelson [18]).…”
Section: Introductionmentioning
confidence: 99%